"The use of bilateral continuous erector spinae plane blocks for postoperative analgesia after right‐sided living donor hepatectomy: A feasibility study". Issue 9 (19th July 2021) - Adelmann, Dieter; Khorashadi, Mina; Zhou, George; Kinjo, Sakura; Braun, Hillary J.; Ascher, Nancy L.; Braehler, Matthias R.
Abstract: Background: Postoperative pain after living donor hepatectomy is significant. Postoperative coagulopathy may limit the use of epidural analgesia, the gold standard for pain control in abdominal surgery. The erector spinae plane block (ESPB) is a novel regional anesthesia technique that has been shown to provide effective analgesia in abdominal surgery. In this study, we examined the effect of continuous ESPB, administered via catheters, on perioperative opioid requirements after right living donor hepatectomies for liver transplantation. Methods: We performed a retrospective cohort study in patients undergoing right living donor hepatectomy. Twenty‐four patients who received preoperative ESPB were compared to 51 historical controls who did not receive regional anesthesia. The primary endpoint was the total amount of oral morphine equivalents (OMEs) required on the day of surgery and postoperative day (POD) 1. Results: Patients in the ESPB group required a lower total amount of OMEs on the day of surgery and POD 1 [141 (107–188) mg] compared the control group [293 (220–380) mg; P  < .001]. Conclusions: The use of continuous ESPB significantly reduced opioid consumption following right living donor hepatectomy.